Digital Transformation in Increasing The Effectiveness of Supervision of The Use of Organic Firearms at The National Police: Implementation of E-Government in The Regional Police of South Sumatra, Indonesia - Akso, Syaparudin; Sobri, Kgs. M.; Azhar, Azhar; Putra, Raniasa (PERSPEKTIF, 2024)
Digital transformation has become the main basis for government agencies to increase the effectiveness of supervision and resource management, including in the context of public security. The Regional Police of South Sumatra, Indonesia, adopted e-government innovations in an effort to increase supervision of the use of organic firearms. This research aims to analyze the implementation of e-government in digital transformation in the regional police force, with a focus on the effectiveness of organic firearms control. The research methods used are documentation analysis, interviews and surveys among police personnel. The research results show that the implementation of e-government has made a significant contribution to increasing the effectiveness of monitoring the use of organic firearms. E-government systems enable more efficient data collection and analysis, enabling more timely and accurate decision-making. In addition, the implementation of e-government also results in greater transparency in the management of organic firearms, strengthening accountability and reducing the risk of misuse. However, challenges faced include the need for adequate technological infrastructure, sufficient training for personnel, and adequate data protection. This research provides valuable insight into how digital transformation, through the implementation of e-government, can increase the effectiveness of organic firearms monitoring and management in the Regional Police of South Sumatra, Indonesia. The implications of these findings can provide a basis for updating related policies and practices at national and local levels, as well as contribute to the literature on digital transformation in the context of public security.